For the use of sound. Film sound analysis for audio-description: some key issues - Aline, Remael (MonTi Monografías de Traducción e Interpretación, 2014)
This article aims to outline the issues involved in the production and reception of film sound with a view to identifying its challenges for audio-description (AD). It thereby hopes to provide insights into the way in which a careful analysis and integration of film sound and sound effects are required for the production of coherence in AD, if it is to function as part of a new filmic text. However, the article also points to the limits of analysis and interpretation, and to the need for reception research as well as collaboration with visually impaired users. A detailed analysis of a scene from Saving Private Ryan (Spielberg 1998), a film that won an Oscar for best sound effect editing, demonstrates how complex and narratively charged the soundscape of a film can be, thereby exposing the challenges for the audio-describer and, again, demonstrating the need for further research involving the target audience.